The Actualization of the Principles of Missionary Work According to 1 Corinthians 9:19-23 - Adiatma, Daniel Lindung; Wijoyo, Sigit; Sutrisno, Sutrisno (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2022)
The issue of Christianity and the local culture has been a discussion that continues to flourish. The issue of the challenge of preaching the Gospel, which was considered incompatible with the spirituality of the local community, has been contested since the first century. Paul, as an apostle, faced the challenge of preaching the gospel because of the exclusivity of early Christianity. This article is aimed at explaining Paul's teachings in 1 Corinthians 9:1-23 from a missiological point of view. This article is aimed at describing how Paul carried out his missionary work in a society of diverse cultures and spiritualities. The author intends to explain it through an exegesis that emphasizes the passage's historical, grammatical, and contextual aspects. Missionary work is a noble task from God. Cultural diversity requires missionaries to be flexible with cultural conditions without compromising the values of biblical theology. The mission does not have to uproot a person from his or her culture but can provide a new interpretation of that culture according to Christian truth. While giving new meaning to culture, the material of the mission must be Christocentric. Flexibility to local culture can reduce the level of resistance from local communities.